Effects of enrichment activities on students' attitudes toward chemistry - Paulite, Benifrancis Peñalosa (1986)
This study was undertaken to assess the effect of enrichment activities on students' attitudes and achievement toward chemistry. Two third year classes of Novaliches High School served as the control group and experimental group for the study. The experimental group used the enrichment activities while the control used the usual laboratory activities in the topic. An achievement test and a chemistry attitude survey form served as pretests and posstests. The experimental group had higher achievement test scores than the control group and proved the effectivity of the use of enrichment activities in the academic development of students. However, there was no significant difference in the scores of the two groups in the attitude towards chemistry test. This may be due to time constraints met by the researcher in conducting lessons.
Thesis (M.A.T. Chemistry)--University of the Philippines, Diliman.
Keywords: Chemistry -- Experiments; Chemistry -- Study and teaching (Secondary) -- Activity programs -- Philippines; High school students -- Philippines -- Attitudes; Activity programs in education -- Philippines